The power of now - Tolle, Eckhart 1948- (Novato, California New World Library, 2001)
A guide to spiritual awakening through "living in the now," being totally aware in each moment.
Introduction -- ch. 1. You are not your mind -- ch. 2. Consciousness : the way out of pain -- ch. 3. Moving deeply into the now -- ch. 4. Mind strategies for avoiding the now -- ch. 5. The state of presence -- ch. 6. The inner body -- ch. 7. Portals into the unmanifested -- ch. 8. Enlightened relationships -- ch. 9. Beyond happiness and unhappiness there is peace -- ch. 10. The meaning of surrender.
Read by the author.
Compact discs.
Duration: 7:30:00.
Unabridged reading by the author.
107326
Keywords: Spiritual life; Spirituality; Self-realization -- Religious aspects; Personal Satisfaction; Books on CD; Audiobooks